Respuesta :
Answer:
(1,0)
Step-by-step explanation:
3x + 6y = 3
7x + 3y = 7
Multiply the second equation by -2
-2( 7x + 3y = 7)
-14x -6y = -14
Add this to the first equation to eliminate y
3x + 6y = 3
-14x -6y = -14
--------------------
-11 x = -11
Divide by -11
x = 1
Now find y
3x + 6y = 3
3 +6y = 3
Subtract 3 from each side
6y = 0
y =0
Answer:
x = 1
y = 0
Step-by-step explanation:
3x + 6y = 3
7x + 3y = 7
=> 3y = 7 - 7x
=> y = -7/3x + 7/3
3x + 6(-7/3x + 7/3) = 3
=> 3x - 14x + 14 = 3
=> -11x = -11
=> -x = -11/11
=> -x = -1
=> x = 1
So, 3(1) + 6y = 3
=> 3 + 6y = 3
=> 6y = 0
=> y = 0/6
=> y = 0
So, x = 1
y = 0